IMPLEMENTASI PROPHETIC LEADERSHIP DI ERA DIGITAL - Amil Salim; Robi yanto; Yuniar Yuniar; Indah Wigati; Nur Ilahiah (Raudhah - Proud To Be Professional, 2023)
In Islam, man is a leader. The true ideal leader has been illustrated by the Prophet Muhammad sollallohu alaihi walasalam as a perfect leadership with prophetic characteristics of sidiq, trust, tablig, and fatonah. Based on this, the study aims to uncover the challenges and opportunities in the implementation of prophetic leadership in Islamic educational institutions in the digital age. The research methods carried out in this research use library research through seven research steps including: 1) Determining research ideas; 2) Collecting information; 3) Strengthening Research focus 4) Classification of research sources; 5) Reading information sources; 6) Reviewing readings; and 7) Creating articles. The study concluded that the challenges of implementing prophetic leadership are Fast Change, Complex Communication, and Strong Competition. Besides, there are also opportunities to implement prophetic leadership, including: Advanced Technology, Easy Access to Information and High Flexibility.